Solusi Numerik Persamaan Difusi dengan Menggunakan Metode Beda Hingga - Sulpiani, Ririn; Widowati, Widowati (JURNAL SAINS DAN MATEMATIKA, 2013)
The developmental process characteristic of the distribution of pressure, enthalpy and temperature on geothermal reservoir can be represented in mathematical models.The basic equation used in the modeling process is the Darcy law and mass equilibrium equations with the physical parameters of the distribution of pressure. Pressure distribution model obtained is a two-dimensional diffusion equation in the form of two-order partial differential equations. Furthermore, the finite difference centered method used to find the numerical solution of theÂ diffusion equation. Â Keywords: Geothermal Reservoir, pressure, Darcy law, finite difference method